The Effect of Profitability Ratio, Solvability Ratio, and Liquidity Ratio on Stock Price at Sector Company Consumer Non-Cyclicals Listed in Indonesia Stock Exchange Period 2017-2021 - Fadrul, Fadrul; Wijaya, Felix Tirta; Natalia, Anita; Estu, Ahmad Zulkarnain; Novitriansyah, Bob; Hadi, Syukri (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
The purpose of this research was to discover, and research the effect of profitability ratio, solvability ratio, and liquidity ratio on stock price at non-cyclical consumer company sectors listed in the Indonesia Stock Exchange period 2017-2021. The sampling technique of this research used purposive sampling, so that the remainder of this sampling research as many as 60 companies of 98 companies. This research is used secondary data. The secondary data usually used of documentation results of the each company. The method used of this research is descriptive analysis test, classic assumption test, model feasibility test, multiple linear regression analysis, and hypothesis test using the application SmartPLS 4. The results of this research are based on the results of the hypothesis test say that profitability ratio and liquidity ratio have a positive and insignificant effect on stock price; and solvency ratio has a negative and significant effect on stock price.